1997
DOI: 10.1097/00006534-199701000-00002
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Parallel Hairline Incisions and Perpendicular Incisions when Performing a Face Lift

Abstract: Our profession has not decided if it is better to incise parallel or perpendicular (at an angle) to hair follicles when performing a brow lift or a face lift. Thirty patients had one side incised parallel and the other side incised perpendicular to hair follicles. Neither the patients nor the examiners knew how each side was incised. By comparing the invisibility, the nonlinearity, the absence of hypopigmentation, and the abundance of hair into and in front of the scar, we obtained statistical proof that if we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(37 citation statements)
references
References 2 publications
0
37
0
Order By: Relevance
“…Herein, we describe extended IBEB, whereby skin excision is extended to a substantial part of intrabrow skin and the intrabrow incision is made perpendicular to the hair shaft. 5 Postoperative regrowth of the eyebrow through the scar covers the incision location and alleviates eyebrow reduction. Although extended IBEB has many advantages, it has some shortcomings.…”
Section: Arch Facial Plast Surg 2011;13(5):327-331mentioning
confidence: 99%
“…Herein, we describe extended IBEB, whereby skin excision is extended to a substantial part of intrabrow skin and the intrabrow incision is made perpendicular to the hair shaft. 5 Postoperative regrowth of the eyebrow through the scar covers the incision location and alleviates eyebrow reduction. Although extended IBEB has many advantages, it has some shortcomings.…”
Section: Arch Facial Plast Surg 2011;13(5):327-331mentioning
confidence: 99%
“…Both these also make the scalp especially suited to the use of saline expanders, sometimes for several weeks or months [130] or even rapid intraoperative expansion [131] . Camirand and Doucet compared parallel and perpendicular hairline incisions, and concluded that incisions perpendicular to the direction of the hair follicle allow hair to grow through the hairline incision and give a more natural cosmetic appearance [132] . More than anywhere else, rotational skin flaps are employed on the scalp to close larger defects and single, double and triple flaps have been described in detail [133] .…”
Section: Special Situations: Scalp and Lower Limbmentioning
confidence: 99%
“…Scalp extension to create sideburns, which are beveled as described by Frechet [17] and scalloped as described by Camirand and Doucet, [18] opens the superior tunnel in a manner that allows for suspension of the SMAS to the temporalis fascia [ Figure 7a]. [19] However, the result is a visible scar that cannot be erased [ Figure 7b].…”
Section: Alpha and Omega Of The Incision Curves Dog-earsmentioning
confidence: 99%
“…The scalloped incision is beveled according to the method of Frechet, in the area of hair-bearing skin. The scalloped incision developed by Camirand and Doucet [18] aids tremendously in dealing with the retroauricular dog-ear. After removing excess skin, the straight long excision edge of the flap is sutured into the scalloped edge, from back to the front, keeping the hairline intact.…”
Section: Alpha and Omega Of The Incision Curves Dog-earsmentioning
confidence: 99%